2021
DOI: 10.1097/phm.0000000000001885
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Rehabilitation Outcomes After Severe COVID-19 Infections

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Consequences of severe COVID-19 infection may require hospitalization [1] and result in impaired physical and cognitive function, as well as limitations in activities of daily living [2][3][4]. These impairments have been shown to be most prominent in elderly patients and patients who have required treatment in intensive care units (ICUs) [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequences of severe COVID-19 infection may require hospitalization [1] and result in impaired physical and cognitive function, as well as limitations in activities of daily living [2][3][4]. These impairments have been shown to be most prominent in elderly patients and patients who have required treatment in intensive care units (ICUs) [2].…”
Section: Introductionmentioning
confidence: 99%
“…These impairments have been shown to be most prominent in elderly patients and patients who have required treatment in intensive care units (ICUs) [2]. Although COVID-19 patients benefit from in-hospital rehabilitation [4], most patients do not qualify for this. Studies have shown promising results in recovery from COVID-19 [5,6], whereas others point out that some groups may still suffer from persisting respiratory impairments [7] and have low participation in society [8].…”
Section: Introductionmentioning
confidence: 99%
“…7 This study's results are consistent with those of Johnson et al, 19 which found that patients with COVID-19 who received a higher frequency of physical therapy services demonstrate improved mobility and increased likelihood of returning home instead of discharge to a rehabilitation facility. 9 Abramoff and colleagues 1 reported that patients who were hospitalized with COVID-19 reached the same functional level upon discharge as those hospitalized without COVID-19. 1 Another study by Busching et al found that rehabilitation can improve physical function and participation in daily activities for patients with COVID-19 including those with severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported positive motor progression and negative correlation between grip strength and the number of days spent in intensive care, both at admission and discharge. In Philadelphia, rehabilitation outcomes of COVID-19 patients ( n = 43) were compared to non–COVID-19 inpatient rehabilitation patients ( n = 247) with impairment codes that were frequent for the COVID-19 patients [ 17 ]. While COVID-19 patients had greater deficits at admission, they eventually reached similar functional outcomes compared with the non–COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%